Global Existence and Large Time Behavior of Solutions to the Bipolar Nonisentropic Euler-Poisson Equations. (27th January 2014) - Chen, Min; Wang, Yiyou; Li, Yeping
Abstract : We study the one-dimensional bipolar nonisentropic Euler-Poisson equations which can model various physical phenomena, such as the propagation of electron and hole in submicron semiconductor devices, the propagation of positive ion and negative ion in plasmas, and the biological transport of ions for channel proteins. We show the existence and large time behavior of global smooth solutions for the initial value problem, when the difference of two particles' initial mass is nonzero, and the far field of two particles' initial temperatures is not the ambient device temperature. This result improves that of Y.-P. Li, for the case that the difference of two particles' initial mass is zero, and the far field of the initial temperature is the ambient device temperature.